Economic and environmental impacts of a large scale water transfer in the Colorado River Basin - Oamek, George, author; Johnson, Stanley R., author; U.S. Committee on Irrigation and Drainage, publisher (Colorado State University. Libraries, 1989)
The direct economic, and offsite environmental impacts of a 400,000 acre foot water transfer between irrigators in the Upper Basin of the Colorado River and urban users in the Lower Basin was examined. Results indicated that the transfer would result in considerable offsite benefits, with minimal disruption to local agriculture.
USCID regional meetings -- 1989
Large scale water transfer
Not digitized by CSUL Digital Services.
Presented at Planning for water shortages: water reallocations and transfers drought management: proceedings from the 1989 regional meetings held on August 24-25, 1989 in Boise, Idaho and on October 19-21, 1989 in St. Louis, Missouri.